Ação Declaratória de Constitucionalidade: expectativa, realidade e algumas propostas - Fábio Carvalho Leite (Revista Interdisciplinar de Direito, 2017)
This paper claims that the declaratory action of constitutionality reveals some undefined points and that its legitimacy depends on the interpretation of theses aspects. These points are identified through the confrontation of doctrinal approach about this action with its application by the Supreme Court. The paper concludes with a critical analysis of these undefined points and some proposals that should be taken into account when trying to untangle them.